Endothelial monolayer disruption in bioprosthetic heart valve as a trigger of primary tissue failure - R. A. Mukhamadiyarov; N. V. Rutkovskaya; A. G. Kutikhin; I. V. Milto; O. D. Sidorova; L. S. Barbarash (Бюллетень сибирской медицины, 2020)
Aim. To study the surface and cellular composition of non-calcified bioprosthetic heart valve (BHV) leaflets with varying degrees of structural deterioration to determine the possible mechanisms of primary tissue failure development.Materials and methods. An examination of six bioprosthetic heart valves (KemCor and PeriCor) extracted from mitral position due to the structural valve deterioration was performed. The structure of BHV leaflets was studied by hematoxylin – eosin staining and immunohistochemistry assay (with the following indicators – CD3, T lymphocytes; CD20, B lymphocytes; CD31, mature endothelial cells; CD34, endothelial progenitor cells; CD68, monocytes/macrophages; vimentin, mesenchymal cells; α-smooth muscle actin, vascular smooth muscle cells).Results. The degree of disruption of BHV leaflets in primary tissue failure differed significantly: relatively intact samples with the intact endothelial monolayer, areas with impairment of the surface layers (minimal and moderate damage) and areas with the spread of destruction into the extracellular matrix of the leaflet (expressed degeneration) were determined. Endothelial cells (monolayer with preserved or impaired integrity), macrophages, smooth muscle cells and other mesenchymal lineage cells were identified in BHV. T- and B-lymphocytes were not detected in the BHV leaflets. Conclusions. A characteristic feature of structurally deteriorated BHVs is impairment of endothelial monolayer integrity in areas of degraded extracellular matrix. In contrast to other types of bioprosthetic dysfunctions, structural valve deterioration was characterized by the absence of lymphocyte infiltration. Therefore, we suppose that endothelial mololayer injury is a trigger of structural BHV deterioration.